DEF dosing for selective catalytic reduction catalysts - QUIGLEY, DAVID P; FUNK, SARAH; HERNANDEZ GARCIA, PABLO E; RADWAN, AMR M (2018)
A method to reduce NOx leakage and NH3 loss is provided when the SCR system is increasing in temperature and/or increasing exhaust gas mass flow. The method includes the steps of monitoring states ofparameters of the exhaust gas upstream of an SCR catalyst, wherein the states of parameters include at least one of the inlet temperature or the exhaust gas mass flow; identifying one of a temperatureincrease or an increased exhaust gas mass flow at the SCR inlet; identifying a new lower ammonia set-point or storage concentration for the SCR; and identifying the rate of NH3 consumption. The method further includes the step of determining an 'intervening phase', a small dosage of DEF is continued during the intervening phase. 提供了种当SCR系统的温度升高和/或废气质量流量增加时减少NO渗漏和NH漏失的方法。该方法包括以下步骤：监测SCR催化剂上游废气的参数状态，其中参数状态包括入口温度或废气质量流量中的至少个；识别SCR入口处的温度升高或废气质量流量增加之；识别SCR的新的低氨设定值或储存浓度；以及识别NH消耗的速率。该方法还包括确定"中间阶段"的步骤，在中间阶段期间持续小剂量的DEF。